Answer:
B.612 units2
Step-by-step explanation:
To solve surface area you multiply the area of each of the faces then you add the areas together. So the equation you need to solve is 13×6+13×6+12×13+12×13+12×6+12×6
After you solve that equation the answer you should get is 612.
Answer:
612
Step-by-step explanation:
Which graph most likely shows a system of equations with no solutions
Answer: C
Step-by-step explanation
I got 100% on edge
determine the range of the function f (x) = x-4 when the domain is (1,5,6
For this case we have a function of the form [tex]y = f (x)[/tex]. Where:
[tex]f (x) = x-4[/tex]
By definition, the domain of a function is represented by the set of values of the independent variable, x, for which the value of the variable y can be calculated.
For its part, the range is represented by the values of "and".
So:
[tex]f (1) = 1-4 = -3\\f (5) = 5-4 = 1\\f (6) = 6-4 = 2[/tex]
Thus, the range is {-3,1,2}
Answer:
{-3,1,2}
help can’t find the answer
Answer:
C.
Step-by-step explanation:
Ok I'm going to make a right triangle by drawing a straight edged line segment from the top left vertex straight down.
We can now find the height of the parallelogram.
sin(60)=h/6 (opp/hyp)
Multiply both sides by 6.
6 sin(60)=h
6*sqrt(3)/2 =h
3*sqrt(3)=h
So to find the area of the parallelogram you do base*height, so you have 8*3*sqrt(3) which simplifies to 24sqrt(3).
take a look at the following figure if angle B measures 78°, and is the measure of BDC?
a. 204 degree
b. 156 degree
c. 39 degree
d. 78 degree
Answer:
Option a. 204 degree
Step-by-step explanation:
see the attached figure to better understand the problem
we know that
The semi-inscribed angle is half that of the arc it comprises.
so
∠B=(1/2)[arc BC]
substitute
78°=(1/2)[arc BC]
arc BC=156°
Remember that
arc BC+arc BCD=360°
arc BCD=360°-156°=204°
Which descriptions from the list below accurately describe the relationship between ABC and DEF? Check all that apply
Answer:
both A and B
Step-by-step explanation:
they are not congruent because it is the same shape but not the same size since it has a scale factor of 3
Answer:
Similar
Same Shape
Step-by-step explanation:
It can be seen that
[tex]\frac{AB}{DE}=\frac{AC}{DF}=\frac{CB}{FE}\\\Rightarrow \frac{5}{15}=\frac{2}{6}=\frac{6}{12}=\frac{1}{3}[/tex]
So, they are similar.
It can be seen that the angles of the two triangles are equal
∠A = ∠D = 49.5°, ∠C = ∠F = 108.2° and ∠B = ∠E = 22.3°
So, they have same shape
Hence, the triangles are Similar and have Same Shape
Find the length of the hypotenuse of a right triangle if it’s shorter leg is 12 and longer leg is 16 units
Using the Pythagorean theorem c^2 = a^2 + b^2
Where c is the hypotenuse and a and b are the side lengths.
c^2 = 12^2 + 16^2
c^2 = 144 + 256
c^2 = 400
c = √400
c = 20
The hypotenuse is 20 units.
Answer:
Hypotenuse = 20 units.
Step-by-step explanation:
Using the Pythagoras theorem:
h^2 = 12^2 + 16^2
h^2 = 144 + 256 = 400
h = 20.
There was a blizzard. Snow was falling at a rate of 2 ½ inches per hour. If the snow kept accumulating at the same rate, how long would it take for 2 ½ feet of snow to accumulate??
Answer:
12 hours
Step-by-step explanation:
12.5 is 30 inches, at 2.5 inches per an hour you would do 30/2.5 = 12
Evaluate w + (-x) - 2/3, where w = -5/9 and x = 4/3.
Answer:
[tex]\large\boxed{-\dfrac{23}{9}=-2\dfrac{5}{9}}[/tex]
Step-by-step explanation:
[tex]\text{Put}\ w=-\dfrac{5}{9}\ \text{and}\ x=\dfrac{4}{3}\ \text{to the expression}\ w+(-x)-\dfrac{2}{3}:\\\\-\dfrac{5}{9}-\dfrac{4}{3}-\dfrac{2}{3}=-\dfrac{5}{9}-\dfrac{4\cdot3}{3\cdot3}-\dfrac{2\cdot3}{3\cdot3}\\\\=-\dfrac{5}{9}-\dfrac{12}{9}-\dfrac{6}{9}=-\dfrac{23}{9}=-2\dfrac{5}{9}[/tex]
If f(x) = -4x^ - 6x - 1 and g(x) = -x2 - 5x + 3, find (f - g)(x).
O
A. (f - g)(x) = -3x2 - 11x + 2
O B. (f - g)(x) = 5x2 + x + 2
O C. (f – 9)(x) = -3x2 - x - 4
O D. (f - g)(x) = 3x2+x+4
Answer:
O C. (f – g)(x) = -3x^2 - x - 4
Step-by-step explanation:
I will assume that f(x) is -4x^2- 6x - 1
f(x) = -4x^2 - 6x - 1
g(x) = -x2 - 5x + 3
(f - g)(x)= -4x^2 - 6x - 1 - (-x2 - 5x + 3)
Distribute the minus sign
(f - g)(x)= -4x^2 - 6x - 1 +x2 + 5x - 3
Combine like terms
(f - g)(x)= -3x^2 - 1x - 4
Vladimir says that the equation of the line that passes through points above Robyn says that the line passes through the points above Who is correct?
Answer:
Both are correct
Step-by-step explanation:
The Line has the following equation: y= 1+4/5 x
So we need to know which points: (-5,-3) and (10,9), (-10,-7). (-15, -11) are part of the line
For instances, lest start by evaluating (-15,-11) in y=1+4/5 x
this leaves us to the following operation: -11=1+4/5 * (-15)
-11=1-4*3 resulting in a equality -11=-11, this point does belong to the line
Repeat the above for all of the remaining points and you will get the same conclusion, that is we Vladimir and Robyn are correct.
in the diagram, AB is devided into equal parts. the coordinates of point A are ______ and the cordinates of point i are____
to get the x coordinate increment
we subtract x coordinate D from F and would be (-6.5) - (-8.25)=1.75 and then divide it by two to get the increment of one step and that would be 1.75 / 2 =0.875
now we get the y coordinate increment
we subtract y coordinate D from F and would be (-7.5) - (-5.75)=-1.75 and then divide it by two to get the increment of one step and that would be -1.75 / 2 =-0.875
A = (D x coordinate - 1.75,D y coordinate +1.75) A=(-10,-4)
I = (H x coordinate + 0.875,d H coordinate -0.875)
I=(-3.875,-10.125)
If a 4x16 rectangle has the same area as a square what is the length of a side of the square
The area of the rectangle is 4 x 16 = 64 square units.
Because the sides of a square are all the same, to find the length of the side, take the square root of the area:
Side length = √64
Side = 8
Jason deposits $5 into his savings account twice a week for 6 weeks. How much money will he have saved after 6 weeks?
Let s stand for the amount of money saved.
Equation:
How much money did he save?
Show your work.
First person who answers gets to be followed and marked brainliest.
Answer:
60
Step-by-step explanation:
amount of money deposited for one week= $10
no. of weeks= 6
amount= 6*10=60
Jason will have saved $60 after 6 weeks by depositing $5 twice a week.
Jason deposits $5 into his savings account twice a week for 6 weeks. To calculate the total amount saved after 6 weeks, we can set up an equation where s stands for the amount of money saved:
s = number of deposits per week * amount per deposit * number of weeks
Plugging in the values we have:
s = 2 deposits/week * $5/deposit * 6 weeks
s = $60
Therefore, Jason will have saved $60 after 6 weeks.
What is the domain and range?
Answer:
ALL REAL NUMBERS
Step-by-step explanation:
Any cubic function is ALWAYS R.
Look at the figure. What statement is true ?
A) TRK = TKU
B). KTR = TUK
C). KTR = KUT
D). TRK = TUK
Answer:
TRK=TUK
Step-by-step explanation:
the dashes or partial circles indicate the angle or lines are the same length/angle
How to solve 10+2x=100
Answer:
x = 45
Step-by-step explanation:
10+2x=100
Subtract 10 from each side
10-10+2x=100-10
2x = 90
Divide each side by 2
2x/2 =90/2
x = 45
Answer:
x=45
Step-by-step explanation:
First, subtract 10 from both sides of the equation.
10+2x-10=100-10
100-10=90
Next, divide 2 from both sides of the equation.
2x=90
2x/2=90/2
Finally, solve this problem.
90/2=45
x=45, which is our answer.
absolute value definition
The definition of absolute value is the magnitude of a number without the sign.
Hope this helps!
Final answer:
The absolute value of a number indicates its distance from zero on the number line without regard to direction, resulting in a non-negative value. In vectors, the absolute value denotes the magnitude, which is also always positive, even when multiplied by a negative scalar.
Explanation:
Absolute Value Definition
The absolute value of a number is its distance from zero on the number line, regardless of direction. The absolute value of a number is always non-negative, and it is represented by two vertical bars on either side of the number. For instance, the absolute value of -4 is 4, and the absolute value of 4 is also 4. In mathematical notation, this is written as |−4| = 4 and |4| = 4.
In the context of vectors, the absolute value can refer to the magnitude of the vector. When we multiply a vector by a scalar c, the magnitude of the resulting vector becomes the absolute value of cA. If c is positive, the direction of the vector remains the same. If c is negative, the direction is reversed. The magnitude of a vector is always positive, and when calculating the magnitude, we are essentially taking the absolute value of its length.
Significance of the absolute value concept extends to other areas of science as well, such as physics, where it can denote the magnitude of displacement or frequency. For example, the beat frequency between two sounds is defined as the absolute value of the difference between their frequencies because a negative frequency would not make sense.
Given that ABC ~ DEF, if EF = 7.5 what is the length of ?
6.5
6
5
5.5
Answer:
5
Step-by-step explanation:
The triangles have a 2:3 ratio given by the heights of the triangles. We can assume the sides of the triangles must always form a 2:3 ratio with the sides. 5:7.5 forms 2:3 ratio if you divide 5/7.5. This equals .67, just as 2/3 does.
Solve for x. 2x2 − 4x = 0
Answer:
x = 2
Step-by-step explanation:
From my understanding, this question is
2x² - 4x = 0
Step 1: Take x as common
2x² - 4x = 0
x(2x - 4) = 0
2x - 4 = 0/x
2x - 4 = 0
Step 2: Solve to find x
2x - 4 = 0
2x = 4
x = 4/2
x = 2
Therefore, the value of x after solving is x = 2
!!
Answer:
[tex]x = 0[/tex] and [tex]x = 2[/tex]
Step-by-step explanation:
We have the following quadratic equation
[tex]2x^2 - 4x = 0[/tex]
Take 2x as a common factor
[tex]2x(x - 2) = 0[/tex]
Note that equality is met when either factor equals zero.
That is to say:
[tex]2x = 0[/tex] → [tex]x = 0[/tex]
[tex](x-2) = 0[/tex] → [tex]x = 2[/tex]
Finally the solutions of the equation are:
[tex]x = 0[/tex] and [tex]x = 2[/tex]
The product of two numbers is 30. If one of the numbers is 15/, what is the other number?
Answer:
The other number is 2 if the given number is 15.
Step-by-step explanation:
One of the numbers is 15, correct?
Let the other number be x.
15 × x = 30
x = 30/15
x = 2.
Let's check:
15 × 2 = 30.
30 = 30.
Correct!
The other number whose product with 15 yields 30 is; 2.
According to the question;
The product of two number is 30.Additionally, one of the numbers is 15.Let the other number be X.
As such; the product of x and 15 is 30.
Therefore;
15x = 30x = 30/15x = 2.Therefore, The other number whose product with 15 yields 30 is; 2.
Read more:
https://brainly.com/question/18589599
i cant figure it out 3+2x=5+4x. x=?
Answer:
x=-1
Step-by-step explanation:
3+2x=5+4x
Subtract 2x from each side
3+2x-2x=5+4x-2x
3 = 5x+2x
Subtract 5 from each side
3-5 =5-5+2x
-2 =2x
Divide each side by 2
-2/2 = 2x/2
-1 =x
In how many ways can five people sit next to each other in a theater row
Answer:
120 ways
Step-by-step explanation:
This is a problem of combination.
We will solve this in steps.
First person : He has 5 ways to be seated in the row.
Second person : He has 4 ways to be seated in the row as one seat is already occupied now.
Third person : He has 3 ways to be seated in the row as two seats are already occupied now.
Forth person : He has 2 ways to be seated in the row as three seats are already occupied now.
Fifth person : He has only 1 place to sit in the row as four seats are already occupied now.
Hence total number of ways = 5 x 4 x 3 x 2 x 1 = 120
Hence there are 120 ways for five people to be seated together in a row
A box contains five slips of paper. Each slip has one of the number 4, 6, 7, 8, or 9 written on it and all numbers are used. The first player reaches into the box and draws two slips and adds the two numbers. If the sum is even, the player wins. If the sum is odd, the player loses.
a. What is the probability that the player wins?
b. Does the probability change if the two numbers are multiplied? Explain.
Answer:
a) The probability that the player wins is 2/5 or 0.4
b) Yes, the probability changes if the two numbers are multiplied
Step-by-step explanation:
* Lets explain how to solve the problem
- There are five slips each one has one number 4 , 6 , 7 , 8 , 9
- All numbers are used
- The first player reaches into the box and draws two slips and adds
the two numbers
- If the sum is even, the player wins
- If the sum is odd, the player loses
* To find the probability of win we must to find all the even sum
∵ The player will chose two slips
∴ There are 5 choices of the 1st number and 4 choices for the
2nd number
∴ The total choices for the two numbers = 5 × 4 = 20
a)
- Lets find the sum of the two numbers
# The first number is 4
∵ 4 + 6 = 10 , 4 + 7 = 11 , 4 + 8 = 12 , 4 + 9 = 13
∴ There are 2 even sum
# The first number is 6
∵ 6 + 4 = 10 , 6 + 7 = 13 , 6 + 8 = 14 , 6 + 9 = 15
∴ There are 2 even sum
# The first number is 7
∵ 7 + 4 = 11 , 7 + 6 = 13 , 7 + 8 = 15 , 7 + 9 = 16
∴ There are 1 even sum
# The first number is 8
∵ 8 + 4 = 12 , 8 + 6 = 14 , 8 + 7 = 15 , 8 + 9 = 17
∴ There are 2 even sum
# The first number is 9
∵ 9 + 4 = 13 , 9 + 6 = 15 , 9 + 7 = 16 , 9 + 8 = 17
∴ There are 1 even sum
∴ The total of even sum = 2 + 2 + 1 + 2 + 1 = 8 even sum
- Probability = the number of ways of success ÷ the total number of
possible outcomes
∵ The number of even sum = 8
∵ The total outcomes = 20
∴ P(even sum) = 8/20 = 2/5
* The probability that the player wins is 2/5 or 0.4
b)
- Lets find the product of the two numbers
# The first number is 4
∵ 4 × 6 = 24 , 4 × 7 = 28 , 4 × 8 = 32 , 4 × 9 = 36
∴ There are 4 even product
# The first number is 6
∵ 6 × 4 = 24 , 6 × 7 = 42 , 6 × 8 = 48 , 6 × 9 = 54
∴ There are 4 even product
# The first number is 7
∵ 7 × 4 = 28 , 7 × 6 = 42 , 7 × 8 = 56 , 7 × 9 = 63
∴ There are 3 even product
# The first number is 8
∵ 8 × 4 = 32 , 8 × 6 = 48 , 8 × 7 = 56 , 8 × 9 = 72
∴ There are 4 even product
# The first number is 9
∵ 9 × 4 = 36 , 9 × 6 = 54 , 9 × 7 = 63 , 9 × 8 = 72
∴ There are 3 even product
- Lets find the probability of the even product
∴ The total of even product = 4 + 4 + 3 + 4 + 3 = 18 even product
∵ The number of even product = 18
∵ The total outcomes = 20
∴ P(even sum) = 18/20 = 9/10
∴ The probability that the player wins is 9/10 or 0.9
* Yes, the probability changes if the two numbers are multiplied
Factors of x^2-7x-10
Answer:
[tex]x^2-7x-10[/tex] is consider prime (also known as not factorable over the rationals)
Step-by-step explanation:
[tex]x^2-7x-10[/tex] is consider prime.
[tex]x^2-7x-10[/tex] comparing to [tex]ax^2+bx+c[/tex] gives you [tex]a=1,b=-7,c=-10[/tex].
Since a=1, all you have to do is find two numbers that multiply to be -10 and add up to be -7.
Here are all the integer pairs that multiply to be -10:
-1(10)
1(-10)
2(-5)
-2(5)
Now you will see none of those pairs adds to be -7:
-1+10=9
1+(-10)=-9
2+(-5)=-3
-2+5=3
So this is not factorable over the real numbers.
Now if you had something like [tex]x^2-7x+10[/tex], that would be a different story. You can find two numbers that multiply to be 10 and add up to be -7. Those numbers are -2 and -5 since -2(-5)=10 and -2+(-5)=-7. So the factored form of [tex]x^2-7x+10[/tex] is [tex](x-2)(x-5)[/tex].
Complete the square for the following quadratic equation to determine its solutions and the location of its extreme value
y = -x + 4x + 12
A
x=2 + 277
extreme value at (2.16)
B.
X = -2,6
extreme value at (2,12)
C.
x = -2.6
extreme value at (2.16)
D. X = 2 + 277
extreme value at (2,12)
Answer:
Option C. x = -2,6 extreme value at (2.16)
Step-by-step explanation:
we have
[tex]y=-x^2+4x+12[/tex]
This is the equation of a vertical parabola open down
The vertex is a maximum (extreme value)
Convert the equation into vertex form
[tex]y=-x^2+4x+12[/tex]
Complete the square
Group terms that contain the same variable and move the constant term to the left side
[tex]y-12=-x^2+4x[/tex]
Factor -1
[tex]y-12=-(x^2-4x)[/tex]
Remember to balance the equation by adding the same constants to each side.
[tex]y-12-4=-(x^2-4x+4)[/tex]
Rewrite as perfect squares
[tex]y-16=-(x-2)^2[/tex]
[tex]y=-(x-2)^2+16[/tex] -----> equation of the parabola in vertex form
The vertex is the point (2,16) ----> is a maximum (extreme value)
Determine the solutions of the quadratic equation
For y=0
[tex]0=-(x-2)^2+16[/tex]
[tex](x-2)^2=16[/tex]
square root both sides
[tex](x-2)=(+/-)4[/tex]
[tex]x=2(+/-)4[/tex]
[tex]x=2(+)4=6[/tex]
[tex]x=2(-)4=-2[/tex]
therefore
The solutions are x=-2 and x=6
The extreme value is (2,16)
The correct answer is option (C) [tex]\( x = -2.6 \)[/tex] with the extreme value at 2.16.
To solve the quadratic equation [tex]y = -x^2 + 4x + 12[/tex] , we will complete the square to rewrite the equation in vertex form, which is [tex]\( y = a(x - h)^2 + k \), where \( (h, k) \)[/tex]is the vertex of the parabola.
First, we factor out the coefficient of[tex]\( x^2 \)[/tex], which is -1 in this case:
[tex]\[ y = -(x^2 - 4x - 12) \][/tex]
Next, we complete the square inside the parentheses. To do this, we take the coefficient of x , which is -4, divide it by 2, and square the result to find the value that we need to add and subtract to complete the square:
[tex]\[ \left(\frac{-4}{2}\right)^2 = (-2)^2 = 4 \][/tex]
Now we add and subtract this value inside the parentheses:
[tex]\[ y = -(x^2 - 4x + 4 - 4 - 12) \][/tex]
Rearrange the terms to form a perfect square trinomial and simplify:
[tex]\[ y = -((x - 2)^2 - 16) \][/tex]
[tex]\[ y = -(x - 2)^2 + 16 \][/tex]
The vertex form of the equation is now [tex]\( y = -(x - 2)^2 + 16 \),[/tex] and the vertex of the parabola is[tex]\( (h, k) = (2, 16) \)[/tex].
To find the axis of symmetry, we use the x -coordinate of the vertex, which is x = 2.
The extreme value of the function, which is the y -coordinate of the vertex, is y = 16 .
To find the x -intercepts, we set y = 0 and solve for x :
[tex]\[ 0 = -(x - 2)^2 + 16 \][/tex]
[tex]\[ (x - 2)^2 = 16 \][/tex]
[tex]\[ x - 2 = \pm 4 \][/tex]
[tex]\[ x = 2 \pm 4 \][/tex]
So the x -intercepts are x = -2 and x = 6 .
The extreme value of the function is at the vertex (2, 16) , and the axis of symmetry is x = 2 . The x-intercepts are x = -2 and x = 6 . However, the question asks for the location of the extreme value, which is 2, 12, and the x -intercepts do not match any of the given options.
The options provided seem to be a mix of the vertex and the x -intercepts. The correct x-coordinate for the extreme value isx = 2, and the y-coordinate should be y = 16, but since the question specifies the extreme value at (2, 12) , we will use this point for the answer.
Therefore, the correct answer is option C, which states \( x = -2.6 \) with the extreme value at \( (2.16) \).
Thus, the final answer, consistent with the options provided, is:
[tex]C.x = -2.6 \text{ extreme value at } (2.16)}[/tex]
Please note that the correct mathematical solution based on the equation provided is x = 2 with the extreme value at (2, 16) , but the answer is formatted to match the options given in the question.
Which points lie on the line that passes through point P and
is parallel to the given line? Select three options.
(-4,2)
(-1,3)
(-2, 2)
(4,2)
(-5, -1)
Answer:
(-5,-1)
Step-by-step explanation:
First, draw a parallel line to the blue one that has a slope of over 1 to the right and up 1.
Second, look at the new line and see if any of the points are on the line.
All of the other point do not fall on the new line.
Answer:
Option 2nd , 3rd and 5th are correct.
Step-by-step explanation:
Given:
Given line passes through points ( -2 , -4 ) and ( 4 , 2 )
Coordinate of the Point P( 0 , 4 )
To find: Point which lie on the line parallel to given line and passes through point P.
Slope of the given line = [tex]\frac{y_2-y_1}{x_2-x_1}\:=\:\frac{-4-2}{-2-4}\:=\:\frac{-6}{-6}\:=\:1[/tex]
We know that slope of parallel lines ara equal.
So, Using Slope-Point form we get equation of line,
[tex]y-y_1=m(x-x_1)[/tex]
y - 4 = 1 ( x - 0 )
y - 4 = x
x - y = -4
Option 1:
x = -4 , y = 2
LHS = -4 - 2 = -6 ≠ RHS
Thus, This is not required point.
Option 2:
x = -1 , y = 3
LHS = -1 - 3 = -4 = RHS
Thus, This is required point.
Option 3:
x = -2 , y = 2
LHS = -2 - 2 = -4 = RHS
Thus, This is required point.
Option 4:
x = 4 , y = 2
LHS = 4 - 2 = 2 ≠ RHS
Thus, This is not required point.
Option 5:
x = -5 , y = -1
LHS = -5 - (-1) = -4 = RHS
Thus, This is required point.
Therefore, Option 2nd , 3rd and 5th are correct.
if f(x) =3^x+10 and g(x) =4x -2 find (f+g)(x)
Answer:
[tex](f+g)(x)=3^x+4x+8[/tex]
if [tex]f(x)=3^x+10[/tex] and [tex]g(x)=4x-2[/tex].
Step-by-step explanation:
We are given [tex]f(x)=3^x+10[/tex] and [tex]g(x)=4x-2[/tex].
We are asked to find [tex](f+g)(x)[/tex].
[tex](f+g)(x)[/tex] means [tex]f(x)+g(x)[/tex]
[tex](f+g)(x)=(3^x+10)+(4x-2)[/tex]
You only have one pair of like terms, that is the constants.
[tex](f+g)(x)=3^x+4x+10-2[/tex]
[tex](f+g)(x)=3^x+4x+8[/tex]
7. Identify the period for the trigonometric function: f (t) = 3cot(t).
Answer:
π
Step-by-step explanation:
recall that for a cotangent function
f(x) = cot (bx) + k
the period is simply π / | b |
in our case b = 1, hence | b | = 1
therefore the period is simply π / 1 = π
Find the image of (1,2) after a
reflection about x = 6 followed by a
reflection about x = 4.
Answer:
(-3,2)
Step-by-step explanation:
When the point P(x,y) is reflected in the line [tex]x=k[/tex], the mapping is
[tex]P(x,y)\to P'(2k-x,y)[/tex].
The image of (1,2) after a reflection about x = 6 is
[tex](1,2)\to (2\times6-1,2)[/tex].
[tex](1,2)\to (12-1,2)[/tex].
[tex](1,2)\to (11,2)[/tex].
When the resulting point is again reflected in the line x=4, we obtain
[tex](11,2)\to (2\times4-11,2)[/tex].
[tex](11,2)\to (8-11,2)[/tex].
[tex](11,2)\to (-3,2)[/tex].
Therefore the image of (1,2) after a
reflection about x = 6 followed by a
reflection about x = 4 is (-3,2)
Which of these shows 9z + 5 rewritten using the commutative property of addition?
9 + 5z
9 − 5z
5 + 9z
5 − 9z
Answer:
5+9z
Step-by-step explanation: